2009
DOI: 10.1007/s10661-009-1077-4
|View full text |Cite
|
Sign up to set email alerts
|

Water quality assessment of Majhiaon block of Garwa district in Jharkhand with special focus on fluoride analysis

Abstract: Fluoride in groundwater is known to contaminate the water sources globally. Jharkhand, one of the states in the eastern part of India, is known to have excessive fluoride content in groundwater sources. The present work involves assessment of water quality with special reference to fluoride in Majhiaon block of Garwa district in Jharkhand. Iron, nitrate and arsenic were also tested for the water samples collected from site. Eight hundred forty samples were tested for fluoride on site using colourimetry method,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…As per Singh et al (2012), F − levels were < 1.0 mg l −1 in most of the samples collected from Dumka and Jamtara Districts in Jharkhand state. Some other districts also in the state have areas where groundwater F − is above the permissible level of BIS ( 2012) (Kumari and Pathak, 2014;Avishek et al 2010;Patolia and Sinha, 2017).…”
Section: Water Quality Assessment For Drinking and Irrigationmentioning
confidence: 99%
“…As per Singh et al (2012), F − levels were < 1.0 mg l −1 in most of the samples collected from Dumka and Jamtara Districts in Jharkhand state. Some other districts also in the state have areas where groundwater F − is above the permissible level of BIS ( 2012) (Kumari and Pathak, 2014;Avishek et al 2010;Patolia and Sinha, 2017).…”
Section: Water Quality Assessment For Drinking and Irrigationmentioning
confidence: 99%
“…The chemical analysis showed that groundwater of Kaithal district in Haryana was hard, alkaline and saline, but it was still within safe limits for domestic use (Goyal, 2010). The Over 50% of the samples contained fluoride higher than the permissible limit (Avishek et al, 2010). Up to 7.85 mg/L Fconcentrations were detected in groundwater near Nagar Parkar Town, Pakistan (Naseem et al, 2010).…”
Section: Vulnerability Of Groundwater and Shallow Aquifermentioning
confidence: 99%
“…Over 50% of the samples contained fluoride higher than the permissible limit (Avishek et al, 2010). Up to 7.85 mg/L Fconcentrations were detected in groundwater near Nagar Parkar Town, Pakistan (Naseem et al, 2010).…”
mentioning
confidence: 99%
“…Most water quality indices rely on normalizing or standardizing, data parameter by parameter according to expected concentrations and some interpretation of 'good' versus 'bad' concentrations (Jacintha et al, 2016). Parameters are often then weighted according to their perceived importance to overall water quality and the index is calculated as the weighted average of all observations of interest (Avishek et al, 2010;Saeedi et al, 2010). The index is a numerical standardized value of evaluation on a certain matter which is in composite form.…”
Section: Introductionmentioning
confidence: 99%